2015
DOI: 10.1097/cad.0000000000000227
|View full text |Cite
|
Sign up to set email alerts
|

Notch 1 promotes cisplatin-resistant gastric cancer formation by upregulating lncRNA AK022798 expression

Abstract: Gastric cancer is now the fourth most common malignancy and the second leading cause of death because of cancer. The resistance to anticancer drugs is the main cause of chemotherapy failure. In this study, we explored the role of Notch 1 and long noncoding RNA (lncRNA) in drug-resistant gastric cancer formation. First, we found that Notch 1 was highly expressed in the cisplatin-resistant gastric cancer cell lines SGC7901/DDP and BGC823/DDP cells. Then, we constructed a Notch 1 overexpression vector plasmid; af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…Zhang et al showed that lncRNA plasmacytoma variant translocation-1 (PVT-1) was highly expressed in gastric cancer tissues from cisplatin-resistant patients and cisplatin-resistant gastric cancer cells; and overexpression of PVT1 in gastric carcinoma promoted the development of MDR (42). Furthermore, Hang et al demonstrated that high expression of lncRNA AK022798 induced by Notch1 resulted in the formation of cisplatin-resistant SGC7901 and BGC823 cells via regulating the expression of ABCC1 and ABCB1 (43). The current study utilized the overexpression of NEAT1 in K562 and THP-1 cell lines to determine the MDR function in response to two different anti-leukemic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al showed that lncRNA plasmacytoma variant translocation-1 (PVT-1) was highly expressed in gastric cancer tissues from cisplatin-resistant patients and cisplatin-resistant gastric cancer cells; and overexpression of PVT1 in gastric carcinoma promoted the development of MDR (42). Furthermore, Hang et al demonstrated that high expression of lncRNA AK022798 induced by Notch1 resulted in the formation of cisplatin-resistant SGC7901 and BGC823 cells via regulating the expression of ABCC1 and ABCB1 (43). The current study utilized the overexpression of NEAT1 in K562 and THP-1 cell lines to determine the MDR function in response to two different anti-leukemic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This previous study also suggested that Notch1 is significantly upregulated in SGC7901/DDP and BGC823/DDP cells (85). The activation of Notch1 via transfection of the Notch1 overexpression vector plasmid may promote lncRNA AK022798 expression and increase the expression of MRP1, P-glycoprotein, and reduce the apoptosis of SGC7901 and BGC823 cells (85). The results of this previous study suggest that Notch1 may promote cisplatin-resistant gastric cancer formation and inhibit apoptosis, at least partially through upregulating the expression of lncRNA AK022798 (85), whilst the regulation mechanism remains unclear.…”
Section: Gastric Cancermentioning
confidence: 65%
“…The silencing of lncRNA AK022798 by specific siRNAs not only decreases the expression of multidrug resistance-associated protein 1 (MRP1) and P-glycoprotein, but also enhances the apoptotic activity of certain cisplatin-resistant gastric cancer cell lines (including SGC7901/DDP and BGC823/DDP cell lines) (85). This previous study also suggested that Notch1 is significantly upregulated in SGC7901/DDP and BGC823/DDP cells (85).…”
Section: Gastric Cancermentioning
confidence: 92%
See 2 more Smart Citations